PENERJEMAHAN KALIMAT IMPERATIF DALAM KOMIK ONE PIECE - Serli Ayuma; Hana Nimashita; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research discussed about the translation of imperative sentences in Japanese language into Bahasa which used in One Piece comic. The aim of this research is to know the imperative sign in the story of One Piece in Japanese language and Bahasa and how it is used in the translation according to Newmark. The object of this research is One Piece comic in Japanese language and Bahasa. This research is a qualitative research which used descriptive method. As the result of this research, it is found that there are eight of imperative signs in Japanese language and five in Bahasa. This research didnot find the different meaning of imperative sentences in Japanese language is receiced well in Bahasa. Beside that, this research used four procedures; transition, modulation, calque and equivalence. The translation procedure which mostly used is calque. It is because the message of the source language will be reveived well in the target language.Key Word : Translation, Imperative Sentences, Comic, One Piece